SmartEdu-Based Science Learning to Foster Collaboration and Problem-Solving - Zulkarnaen, Rizki Hadiwijaya; Mulyani, Hanifah; Ayuni, Resti; Nurdin, Taufik Ali (International Conference on Elementary Education, 2025)
This study explores the implementation of the SmartEdu application as aninnovative digital platform to enhance collaboration and problem-solving skills among pre service elementary teachers in science learning. Using a qualitative case study approach, data were gathered through observation, interviews, and document analysis to investigate how SmartEdu supports interactive and reflective learning experiences. The results reveal that theintegration of SmartEdu facilitates active engagement, teamwork, and analytical reasoning, enabling students to construct knowledge through meaningful interaction and contextual exploration. Furthermore, the digital environment encourages independent inquiry and critical reflection, which strengthen students’ ability to connect scientific concepts with real-life contexts. These findings indicate that SmartEdu-based science learning not only improves students’ collaborative and problem-solving abilities but also nurtures deeper understanding and higher-order thinking, which are essential competencies for future educators in the 21st century.